2020
DOI: 10.1096/fj.201903270r
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous peptides are able to penetrate human cell and mitochondrial membranes, stabilize mitochondrial tRNA structures, and rescue severe mitochondrial defects

Abstract: Mutations in mitochondrial transfer RNA (mt‐tRNA) genes are responsible for a wide range of syndromes, for which no effective treatment is available. We previously reported that transfection of the nucleotide sequence encoding for the 16‐residue β32_33 peptide from mitochondrial leucyl‐tRNA synthetase ameliorates the cell phenotype caused by the mitochondrial tRNA mutations. In this work, we demonstrated that both the β32_33 peptide linked with the known (L)‐Phe‐(D)‐Arg‐(L)‐Phe‐(L)‐Lys (FrFK) mitochondrial pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Here, as a starting point of our investigation, we showed that overexpressed Cterm was capable to interact with the mutated cognate mt-tRNALeu (UUR) in cultured cybrids; this finding is in line with the obtained in vitro results and proposed chaperonic effect of Cterm domain [ 14 , 15 , 16 , 17 ]. Then, we assessed whether Cterm was able to relieve mitochondrial molecular defects in a MELAS cell line characterised by depressed mitochondrial translation.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Here, as a starting point of our investigation, we showed that overexpressed Cterm was capable to interact with the mutated cognate mt-tRNALeu (UUR) in cultured cybrids; this finding is in line with the obtained in vitro results and proposed chaperonic effect of Cterm domain [ 14 , 15 , 16 , 17 ]. Then, we assessed whether Cterm was able to relieve mitochondrial molecular defects in a MELAS cell line characterised by depressed mitochondrial translation.…”
Section: Discussionsupporting
confidence: 81%
“…We also evaluated the effect of Cterm overexpression on a range of mitochondrial processes such as mitochondrial translation, steady-state level and aminoacylation efficiency of mt-tRNALeu (UUR) , bioenergetics, and mitophagy. In agreement with previous findings [ 14 , 15 , 16 , 17 ], a complete recovery of cell viability was observed. Unexpectedly, despite an improvement of protein synthesis, the other analysed mitochondrial processes were not affected by Cterm expression.…”
Section: Introductionsupporting
confidence: 93%
See 3 more Smart Citations